Existence of Solutions for a Periodic Boundary ValueProblem with Impulse and Fractional Derivative Dependence - Yaohong Li; Yongqing Wang; Donal O’Regan; Jiafa Xu (Journal of Mathematics, 2020)
In this paper, we present some theorems on impulsive periodic boundary value problems with fractional derivative dependence. In particular, we discuss the existence of solutions of a class of fractional-order impulsive periodic boundary values with nonlinear terms and impulsive terms satisfying certain growth conditions. Three examples are provided to illustrate our results.